2009
DOI: 10.1088/1748-9326/4/4/045016
|View full text |Cite
|
Sign up to set email alerts
|

Paleoclimatic reconstructions for the south of Valdai Hills (European Russia) as paleo-analogs of possible regional vegetation changes under global warming

Abstract: The possible response of forest ecosystems of south taiga at the south of Valdai Hills on projected future global warming was assessed using analysis of pollen, plant macrofossil and radiocarbon data from four profiles of buried organic sediments of the last interglacial and several cores from modern raised bogs and two small forest mires in the Central Forest State Natural Biosphere Reserve (CFSNBR; Twer region, Russia). The future pattern of climatic conditions for the period up to 2100 was derived using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 4 publications
2
34
1
Order By: Relevance
“…Pollen analysis for central European Russia showed that in the second half of the Holocene (4500-0 14 C year BP), the increasing winter temperature resulted in the expansion of mixed coniferous broad-leaved forests, while cooling and moistening of the area resulted in an increasing area of pure spruce forests and the development of oligotrophic sphagnum bogs [51]. Under excessive moistening, some types of bogs exhibit intensive vertical growth, carbon accumulation, and may expand rapidly toward surrounding forests [25].…”
Section: Discussionmentioning
confidence: 99%
“…Pollen analysis for central European Russia showed that in the second half of the Holocene (4500-0 14 C year BP), the increasing winter temperature resulted in the expansion of mixed coniferous broad-leaved forests, while cooling and moistening of the area resulted in an increasing area of pure spruce forests and the development of oligotrophic sphagnum bogs [51]. Under excessive moistening, some types of bogs exhibit intensive vertical growth, carbon accumulation, and may expand rapidly toward surrounding forests [25].…”
Section: Discussionmentioning
confidence: 99%
“…Our reconstructions of vegetation and climatic changes were based on previously published pollen records from the Staroselsky moch, Klukva mires, and Galich Lake (Velichko et al, 2001;Novenko et al, 2009bNovenko et al, , 2014a. The core chronologies were determined by radiocarbon dating, which was performed in the Radiocarbon Laboratory of the Institute of Geography of the Russian Academy of Science (Staroselsky moch and Klukva mires) and in the Leibniz-Laboratory for Radiometric Dating and Stable Isotope Research, the University of Kiel (Galich Lake, Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The lowermost radiocarbon age of the peat deposits is 9730 ± 100 cal BP. Pollen and plant macrofossil analysis and radiocarbon dating of this borehole have been presented in detail in Novenko et al (2009bNovenko et al ( , 2014a.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations